Nations have the right to kill: Hitler, the Holocaust, and war - Koenigsberg, Richard A. (Library of Social Science, 2009)
Part I: The Holocaust -- The logic of the Holocaust -- Jewish disease within the German body politic -- Devotion to Germany -- Jewish individualism as negation of the German community -- Who shall live and who shall die? -- Jews too shall die -- The sacrificial meaning of the Holocaust -- Worshipping Germany -- Jewish destructiveness -- War as a sacrificial ritual -- The duty to lay down one's life -- Soldiers as sacrificial victims -- The right to destroy millions of men -- Die for Germany--or be killed -- Part II: War -- As the soldier dies, so the nation comes alive -- Obfuscation in the depiction of warfare -- The magnitude of destruction and futility of the First World War -- What was going on? -- Reification of the nation-state -- Willingness to die as declaration of devotion -- As the soldier dies, so the nation comes alive -- Virility and slaughter -- The First World War as perpetual slaughter -- Doctrine of the "offensive at all costs" -- The Battle of the Somme -- Virility, the Battle of Verdun -- The sacred ideal -- Virility and slaughter -- Aztec warfare, western warfare -- Aztec warfare -- The First World War -- Why the perpetual slaughter? -- The body and blood of the soldier gives rise to the reality of the nation -- War as potlatch -- Warfare as truth -- The nation-state kills its own soldiers -- Part III: The logic of war and genocide -- Dying for the country -- Why did hitler wage war? -- Identity of self and nation -- Aryan willingness for self-sacrifice -- Hitler's experience of the First World War -- Willingness to die for one's country -- Why do the best human beings die in war while the worst survive? -- Jewish "shirkers" -- As German soldiers die, so must Jews -- Sacrificial death stripped of honor -- The logic of mass murder -- The First World War -- Hitler and the First World War -- The euthanasia program -- Obedience (unto death) -- Hitler goes to war -- The explanation